2001
DOI: 10.1093/nar/29.20.4114
|View full text |Cite
|
Sign up to set email alerts
|

The role of acetylation in rDNA transcription

Abstract: Treatment of NIH 3T3 cells with trichostatin A (TSA), an inhibitor of histone deacetylase (HDAC), resulted in a dose-dependent increase in transcription from a rDNA reporter and from endogenous rRNA genes. Chromatin immunoprecipitation using anti-acetyl-histone H4 antibodies demonstrated a direct effect of TSA on the acetylation state of the ribosomal chromatin. TSA did not reverse inhibition of transcription from the rDNA reporter by retinoblastoma (Rb) protein, suggesting that the main mechanism by which Rb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
55
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 74 publications
5
55
0
Order By: Relevance
“…The HAT function of p300/CBP was shown to be required for transcription activation in vivo (29,39) and in vitro (1,2,19,31,33). While p300/CBP has also been implicated in the stimulation of Pol I activity (20), no function in Pol III transcription has been reported to date.…”
mentioning
confidence: 99%
“…The HAT function of p300/CBP was shown to be required for transcription activation in vivo (29,39) and in vitro (1,2,19,31,33). While p300/CBP has also been implicated in the stimulation of Pol I activity (20), no function in Pol III transcription has been reported to date.…”
mentioning
confidence: 99%
“…In addition, several groups as well as our own have previously shown multiple levels of epigenetic regulation of rRNA gene expression: rRNA gene expression is inhibited by DNA methylation; 38 MBD3 marks active copies of rRNA genes for demethylation and maintains their demethylated states; 9 histone H4 acetylation at the rRNA promoter marks active alleles of rRNA genes. 10 We have shown that the state of methylation of rRNA genes is critical for their expression and that modulation of MBD3 levels results in changes in methylation of rRNA genes and their expression. 9 The remaining question was whether these epigenetic marks fluctuate during the cell cycle.…”
Section: Discussionmentioning
confidence: 94%
“…Similar to genes transcribed by RNA polymerase II (Pol II), rRNA transcription is induced by the addition of trichostatin A (TSA), a histone deacetylase inhibitor, which leads to increased histone 4 acetylation. 10 We therefore delineated the state of H4 acetylation at the rRNA promoters at different points in the cell cycle. Using chromatin immunoprecipitation (ChIP) assays with antibodies directed against acetylated histone 4 (AcH4) we found that the levels of AcH4 peaks at t = 0, decreases at t = 6, but increases again at t = 10 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding of UBF (14 -16) and possibly a second molecule of SL1 to the upstream promoter element is required for template commitment and efficient transcription in vitro. Both SL1 and UBF are subject to regulation via phosphorylation and acetylation (17)(18)(19)(20)(21)(22). In addition, Rb, the protein product of the retinoblastoma susceptibility gene, interacts with UBF and prevents UBF-dependent activation of rDNA * This work was supported, in whole or in part, by National Institutes of Health Grants GM069841 and HL077814 (to L. I. R.) and GM084946 (to D. A. S.).…”
mentioning
confidence: 99%